Rancang Bangun Alat Pendeteksi Kandungan Alkohol Pada Bahan Pangan Menggunakan Sensor MQ3 - Ujang Wiharja; Danu Permana Aji (JURNAL ELEKTRO, 2024)
Starting from public concerns about access to liquor or alcohol that has been very easy to find its existence which is feared will cause negative effects in the community itself. With the rapid development of the world of electronics, it is able to create various developing components, based on these problems, research with the title design of alcohol detection devices in foodstuffs using MQ3 sensors is expected to overcome problems related to food and beverage products that are detected or alcoholic using MQ3 sensor components, microcontroller, Arduino Uno, LED, LCD, and Buzzer can be made a simple tool to detect alcohol content. The MQ3 sensor has a resistance value whose value can change when it detects methane gas and alcohol in the air. The sensitive material used is SnO2 where the conductivity will be low in clean air according to the results of research that has been done. The test uses cassava, sticky rice, wine, apple cider or vinegar, rice wine as the object of research. The tool that has been made has an error value of 8.05% and for its accuracy of 91.95%. At a certain distance, the MQ3 sensor cannot detect or read alcohol levels.